Analysis of physiological determinants during an international Brazilian Jiu-jitsu competition - Diaz-Lara, F. J.; Del Coso, J.; Garcia, J. M.; Abian-Vicen, J. (International Journal of Performance Analysis in Sport, 2015)
The aim of this study was to determine the physical and physiological demands of a Brazilian Jiu-Jitsu (BJJ) competition. Twenty-six expert male BJJ athletes competing in the 2013 European Open Jiu-Jitsu Championship participated in the study. Before and after an official fight, maximal handgrip strength and maximal height during a countermovement jump (CMJ) were measured. Blood samples were obtained just after the fight and after 10 min of passive recovery to assess blood lactate concentration and clearance. Handgrip force (from 49.65 to 44.85 kgf; P -1) was progressively cleared at a rate of 0.45 ± 0.2 mmol·L-1·min-1. In conclusion, an official BJJ fight causes measurable muscle fatigue in both upper- and lower-body extremities. Moreover, energy production during a BJJ fight greatly relies on the glycolytic pathway and thus the rate of blood lactate clearance could be a determinant physiological factor for success in this sport.